Institutionalization of Multicultural Values in Religious Education in Inclusive Schools, Indonesia - Indriyani Ma'rifah; Sibawaihi (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – Sekolah Tumbuh, an educational institution in Yogyakarta, is characterized as an inclusive school that encourages respect for diversity and difference. This study aims to investigate how multicultural values in Sekolah Tumbuh are integrated into educational aspects, allowing them to incarnate as a form of institutionalization. Design/methods/approach – This study used a phenomenological approach in qualitative methods. The data collection methods involved observation, in-depth interviews, and documentation. The number of respondents was 25 people, including the school principal, religious teachers, students, and employees of Sekolah Tumbuh. Findings – The data analysis results have shown that the institutionalization of multicultural values in Sekolah Tumbuh is in the form of systematics. This process involves a series of solid commitments, massive internalization of values, and institutionalization in the school's vision and mission. All school residents have a strong responsibility and commit to implementing these multicultural values. Research implications/limitations – The best practices carried out by Sekolah Tumbuh can be used as a role model for other schools. These findings have positive implications for the development of multicultural education at the institutional level. Originality/value – This study has contributed to an in-depth understanding of how multicultural values in Sekolah Tumbuh are integrated into aspects of education, including religious education and being institutionalized. Also, this study's results contribute to the development of the concept of multicultural education in Indonesia.